Estrategias de marketing digital en el posicionamiento de los emprendimientos turísticos en la sub cuenca del río Mosquito-Chone - Ponce Laje, Oscar Neptalí (2023)
The research was developed with the goal of designing digital marketing strategies for the positioning of tourism ventures in the Mosquito River sub-basin, Chone canton; It was of a non experiential exploratory level, with a mixed approach, composed of three phases, starting with a tourist diagnosis, characterizing the study area, analyzing offer and demand, considering the historical-logical and descriptive method, field visits, characterization sheet, surveys and interviews. In the second phase, marketing management was analyzed, analyzing the intervention of different digital tools in tourism ventures, applying the synthetic analytical method and the review of metrics. Finally, through a SWOT it was possible to know the qualities and shortcomings of the ventures in relation to digital marketing, strategies were defined and an operational plan was proposed. The following results were obtained: The community presents deficiencies to sustain the tourist activity, due to the low supply of basic services, the habitants are mainly dedicated to agriculture and livestock; The enterprises present deficiencies essentially in the management of digital marketing through social networks, there is little promotion and visibility of the services they offer, the publications present limited management. Based on the swot analysis, six marketing strategies were defined to position tourism ventures, these consist of developing new adaptations in the management of social networks; Under this aspect, the implementation of computer systems is essential so that local enterprises have greater visibility in the market.